Implementasi Sistem Informasi Data Kependudukan Desa Selokerto Berbasis Website dengan Metode Waterfall - Wahyuningsih, Endang; Najib, Abdullah Jabir (Jurnal Kridatama Sains dan Teknologi, 2024)
The use of technology and information is growing rapidly. Many institutions including government agencies have implemented website-based information systems in their services. With this information system, services become faster and more precise. The Selokerto Village Government is one of the villages in Sempor Sub-district, Kebumen Regency, which has implemented a website-based information system to serve peoples need such as requests for letters through the village government administration. However, sometimes the existing system experiences interruptions that cannot be predicted for how long. Data that has been inputted cannot be accessed and cannot print the required letter. The Selokerto Village Government must wait for repairs from the Kebumen Regency Government operator. This makes the Selokerto Village Government unable to provide maximum service. Therefore, another information system is needed with a simple interface design, easy for users to understand, and can accommodate the needs of peoples. The purpose of this research is to implement a website-based Selokerto Village administration information system. The development method used in this research is the waterfall method which consists of five development stages, namely: (1) Analysis, (2) Design, (3) Implementation, (4) Testing, and (5) Maintenance. After the information system is completed, blackbox testing and testing to prospective users of the system are carried out to see the feasibility of the system. This research produces a website-based Selokerto Village administration information system that can be used by Selokerto Village officials to serve the needs of peoples, especially for correspondence purposes. In addition, based on the results of blackbox testing and testing by prospective users, it shows that the system has run well and as expected. Thus it can be said that this system is feasible to implement.Keywords: information system, website, waterfall, village mail administration